Pengaruh Konsentrasi Susu Skim Terhadap Karakteristik Minuman Probiotik Susu Jagung Manis (Zea mays L. Saccharata) Terfermentasi dengan Lactobacillus rhamnosus SKG34 - Kafa Hakiki, Fahmy; Nocianitri, Komang Ayu; Hatiningsih, Sayi (Jurnal Ilmu dan Teknologi Pangan (ITEPA), 2022)
This research was to determine the effect of skim milk concentration on the characteristics of fermented sweet corn milk probiotic drink with Lactobacillus rhamnosus SKG34, and to identify the right skim milk concentration that produced fermented sweet corn milk probiotic drink with the best characteristics. This research method used a Completely Randomized Design (CRD) with skim milk concentration as a treatment that consisted of 6 levels (0%, 3%, 6%, 9%, 12% and 15%). Each treatment was repeated 3 times resulting in 18 experimental units. The data were analyzed by Analysis of Variance (ANOVA) method and if the treatment had a significant effect, then continued with the Duncan Multiple Range Test (DMRT). The results showed that skim milk concentration had a significant effect in total LAB, total sugar, total acidity, pH, and sensory profile. The addition of 9% skim milk concentration produced the best characteristics of fermented sweet corn milk probiotic drink, with the following criteria: 14,60 Log CFU/ml or 7,64 x 1014 CFU/ml of total lactic acid bacteria, 0,63% of total acid, 11,92% of total sugar, 4,42 of pH, with sensory characteristics produced which are white and slightly yellow of colour and liked, aroma was rather liked, texture was thick and liked, taste was sour and liked, and overall acceptance was liked.